Hubungan Antara Tingkat Kecemasan Dengan Prestasi Belajar Matematika Kelas XI Di SMK Negeri 1 Kaligondang Purbalingga - Rofi'i, Najib, dr. Rh. Budhi Muljanto, Sp. KJ, dr. Erna Herawati, Sp. K.J (2015)
Background : Teen age is a period where a process of personality and psychological changes so as susceptible with the high levels of anxiety. Anxiety is one of the risk factors can affect the learning process, especially math. Because of the learning of mathematics need a high concentrations and comprehension to rearch an optimal achievement in mathematics study need conducive conditions. Objective : To analyze the relationship between anxiety level and mathematics learning achievement of XI grade Science Class of Female Student at SMK Negeri 1 Kaligondang Purbalingga. Methods : This study used observational analytic witch cross sectional approach, Total observasional population were 373 students, and the number of sample were 96 respondents who met the inclusion criteria, by using a simple random sampling technique. Then respondent fill out the instrument to get data. Data were analyzed by correlation Spearman. Result : From the analysis of the data showed p value < 0,05 that was equal to 0,001 and r 0,329 that have significant value indicates there was a relationship between anxiety level with mathematics learning achievement of XI grade Science Class of Female Student at SMK Negeri 1 Kaligondang Purbalingga. Conclusion : There was a relationship between anxiety level and mathematics learning achievement of XI grade Science Class of Student at SMK Negeri 1 Kaligondang Purbalingga